THE ROLE OF THE" KUNAUNG "ORAL LITERATURE IN KERINCI FAMILY AND SOCIETY ETHICS: PERAN LITERATUR KUNAUNG LISAN DI KELUARGA KERINCI DAN ETNIK MASYARAKAT - Ria Agustina (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
This research is motivated by the fact that oral literature in the form of Kunaung has ethics as a guideline for behavior in the life of the Kerinci community. The ethics contained in the kunaung serve as guidelines for behavior and the structure of the Kerinci family and community. However, due to the rapid development of science and technology today, oral literature like Kunaung has been neglected. For this reason, tactics are needed in order the existence of oral literature is not obsolete. research is done to answer the research questions which were: how was the embodiment of ethics in the family and society order found in Kunaung. This study aimed to describe the ethics found in Kunaung both in the family and society order. The method used in this research was descriptive method which described ethics both in the family and social order in Kunaung. The research data was in the form of sentences and paragraphs both in narrative and dialogue form. This data was collected based on qualitative methods. Ethics in Kunaung appear implicitly both in the family and social order. The ethics that appeared implicitly in the family order were affection, devotion to parents and responsibility. Meanwhile, ethics in the social order that appeared implicitly were mutual cooperation, adherence to traditional institutions, and wisdom. The results of this study academically provide information to reader about ethics in the Kerinci family and society in kunaung, to add the repertoire of oral literature regarding ethics in the Kerinci’s family and society.